Proximate Biochemical Composition and Antinutritional Analyses of the Selected Parts of Yacon (Smallanthus Sonchifolius) - Gonzales, Merlyn Galagar; Rosario, Romeo Macaltao Del; Walag, Angelo Mark Po (Asian Journal of Biological and Life Sciences)
Aim/Background: Yacon (Smallanthus sonchifolius) is an herbaceous and tuberous perennial plant that belongs to the sunflower family. This study aimed to determine the proximate biochemical and anti-nutritional compositions of the selected parts of mature yacon plants grown in Doalnara Aposkahoy Claveria, Misamis Oriental. Materials and Methods: For the biochemical composition, the selected parts of yacon were analyzed in terms of dry ash (using a furnace), crude lipid (using the Soxhlet extraction method), crude protein (using the Kjeldahl technique), and carbohydrate (calculating the percent difference) using the AOAC methods of proximate analyses. Meanwhile, the antinutritional composition determines alkaloids (using the alkaline precipitation gravimetric technique), oxalates (using the titration method), and phytates (using the Lucas and Markaka procedure) contents. Results: Findings of the overall biochemical composition indicated that carbohydrates came out as the highest (77.97%) followed by ash (9.96%), protein (8.91%), and lipid (3.18%). Comparing the different plant parts, the flowers and leaves registered the higher proteins and lipids contents while tubers showed the highest carbohydrate content and the leaves the highest ash content. Results also showed significant differences in protein, lipid, ash, and carbohydrate contents on the selected parts of yacon. These differences in the biochemical composition of the different parts may be due to the differences in biological functions. On the other hand, the anti-nutritional analyses indicated that oxalates had the highest concentration followed by alkaloids and lastly phytates. The flowers of yacon have shown the highest oxalate content while stems, tubers and tuber peels displayed higher alkaloid contents. Conclusion: Overall, the yacon parts that have promising biochemical and antinutritional compositions are the flowers in terms of protein, lipid, and oxalate contents; leaves for the ash and phytate contents; tubers for the carbohydrate contents; and stems for the alkaloid contents.
Keywords: Alkaloids; Antinutritional analysis.; Oxalates; Phytates; Proximate biochemical composition